Structural Analysis of Powder Complex of Cu(bipy)3(CF3SO3)2(H2O)x (x = 0.5, 1) - Cahyorini Kusumawardani (Science Faculty of Chiang Mai University, 2019)
The powder complex of tris-bipyridinecopper(II) trifluoromethanesulfonate quasi hydrate has been synthesized by the interaction of the corresponding nitrate salt and slightly excess of bipyridine in aqueous solution with drops of ethanol, whereupon the precipitate was produced by addition of an excess of saturated potassium triflate solution on reducing the solvent. AAS measurement showed the content of metal to be 7.54 % corresponding to the theoretical value of 7.56 % in Cu(bipy)3(CF3SO3)2(H2O)x (x = 0.5, 1). The analysis of conductance producing the charge ratio of cation by anion to be 2: 1, clearly confirms the formula. The magnetic moment, µeff, of this complex which was to be 1.73-1.83 B.M, indicates that the complex is paramagnetic corresponding to an unpaired electron. UV-Vis spectrum of the complex reveals the only one absorption observed at about 681.50 nm (14673.51 cm-1), being associated with the spin allowed transition, 2Eg ® 2T2g. The extinction coefficient of 57.8 Lmol-1cm-1 indicates the adoption of the octahedral environment in this complex. The infrared spectrum shows absorptions of ligand group which is influenced by the metal-ligand interaction in this complex. The powder XRD analysis of this complex was refined by Le Bail method of Rietica program and found to be fit as monoclinic crystal system with space group of C2/c, and cell parameters of a = 13.662 Å, b = 23.040 Å, c = 29.268 Å, = 90°, β = 100.15°, = 90°, V = 9069.05 Å3, Rp = 5.5, and Rwp = 9.94 and Rexp = 2.68 leading to χ2 (GOF) value of 13.72. The goodness of the fitting might be also reflected by the derived Bragg R-Factor of 0.02.